World Travel - Iyad Ramlawi; Waseem Mustafa (My University, 2005)
our site "World Travel" to provide traveling services around the world, the traveling services include online car rent service, flight tickets service, hotel reservation service. Also we provide the dynamic administration services and accounts for the companies as well as the site administrator services and accounts; each of these parts has its own profile, permissions, services and data as described in the following section.

our site "World Travel" to provide traveling services around the world, the traveling services include online car rent service, flight tickets service, hotel reservation service. Also we provide the dynamic administration services and accounts for the companies as well as the site administrator services and accounts; each of these parts has its own profile, permissions, services and data as described in the following section.
World Travel